Identification and Quantification of Dityrosine in Grain Proteins by Isotope Dilution Liquid Chromatography-Tandem Mass Spectrometry - Nguyen, D.; Johnson, Stuart; Clarke, M. (2017)
A novel liquid chromatography-tandem mass spectrometry method was developed and validated for identification and quantification of dityrosine in zein protein. The zein samples spiked with a dityrosine standard and 3,3-13C6-dityrosine, as the internal standard were hydrolysed in a mixture of 6 N hydrochloric acid and propionic acid followed by cleaning-up using Sep Pak C18 cartridges. Good linear regression (R2 = 0.999) was obtained in the range 1–1000 ng/mL. Method limit of detection and method limit of quantification were 42.1 and 140 ng/g, respectively. Recoveries were from 92 to 95.2%. Precision and inter-day reproducibility expressed as relative standard deviation were from 3.9 to 22.1% and from 4.4 to 16.6%, respectively. The validated method was applied to quantify dityrosine in various grain proteins. The levels of dityrosine ranged from 0.38 to 1.92 ng/mg. This validated method will be of great value for understanding the role of dityrosine in grain food texture.